Adolescent ambivalence about diabetes technology—The Janus faces of automated care. Issue 8 (9th October 2022) - Cameron, Fergus J.; Arnold, Michael; Gregory, John W.
Abstract: The Janus face metaphor approach highlights that a technology may simultaneously have two opposite faces or properties with unforeseen paradoxes within human‐technology interaction. Suboptimal acceptance and clinical outcomes are sometimes seen in adolescents who use diabetes‐related technologies. A traditional linear techno‐determinist model of technology use would ascribe these unintended outcomes to suboptimal technology, suboptimal patient behavior, or suboptimal outcome measures. This paradigm has demonstratively not been successful at universally improving clinical outcomes over the last two decades. Alternatively, the Janus face metaphor moves away from a linear techno‐determinist model and focuses on the dynamic interaction of the human condition and technology. Specifically, it can be used to understand variance in adoption or successful use of diabetes‐related technology and to retrospectively understand suboptimal outcomes. The Janus face metaphor also allows for a prospective exploration of potential impacts of diabetes‐related technology by patients, families, and their doctors so as to anticipate and minimize potential subsequent tensions.